Multifunctional Biomimetic Nanocarriers for Dual‐Targeted Immuno‐Gene Therapy Against Hepatocellular Carcinoma - Yupeng Sun; Yan Liu; Rui Li; Cuilin Zhang; Ming Wu; Xiaolong Zhang; Aixian Zheng; Naishun Liao; Youshi Zheng; Haipo Xu; Rui Zeng; Yongyi Zeng; et al. (Advanced Science)
Abstract Growing evidences have proved that tumors evade recognition and attack by the immune system through immune escape mechanisms, and PDL1/Pbrm1 genes have a strong correlation with poor response or resistance to immune checkpoint blockade (ICB) therapy. Herein, a multifunctional biomimetic nanocarrier (siRNA‐CaP@PD1‐NVs) is developed, which can not only enhance the cytotoxic activity of immune cells by blocking PD1/PDL1 axis, but also reduce tumor immune escape via Pbrm1/PDL1 gene silencing, leading to a significant improvement in tumor immunosuppressive microenvironment. Consequently, the nanocarrier promotes DC cell maturation, enhances the infiltration and activity of CD8+ T cells, and forms long‐term immune memory, which can effectively inhibit tumor growth or even eliminate tumors, and prevent tumor recurrence and metastasis. Overall, this study presents a powerful strategy for co‐delivery of siRNA drugs, immune adjuvant, and immune checkpoint inhibitors, and holds great promise for improving the effectiveness and safety of current immunotherapy regimens.